SUSTAINABILITY REPORTING DAN KEWAJIBAN PAJAK : PERAN STANDAR GRI DAN SASB PADA PERUSAHAAN INDONESIA MELALUI PENDEKATAN LITERATUR REVIEW - Adie Tirtakusuma; Rimi Gusliana Mais (Bajang Institute, 2025)
In the modern business landscape, sustainability reporting has gained importance as companies are increasingly evaluated not only on financial performance but also on their environmental and social responsibilities. This reporting provides information on the economic, social, and environmental performance of companies, which directly relates to tax compliance. This study employs a literature review approach to explore the role of the International Reporting Initiative (GRI) and Sustainability Accounting Standards Board (SASB) standards in enhancing corporate tax transparency and compliance. Through GRI standards, companies disclose social, economic, and environmental data comprehensively on 2019-2023, while SASB focuses on industry-relevant information. Findings indicate that companies consistently implementing GRI and SASB standards tend to exhibit higher tax compliance and more positive relationships with tax authorities. High-quality sustainability reporting also bolsters corporate reputation among the public and stakeholders, reinforcing commitment to sustainability. However, the implementation of these standards presents challenges in terms of cost and complexity, particularly for small and medium enterprises. Effective, standards-based reporting minimizes tax-related risks while supporting the broader sustainability goals of the company.